PENGARUH MOTIVASI, PENGEMBANGAN KARIR, DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI PADA BANK JATENG CABANG PATI - Teguh Ikkang Purnomo, 11.05.51.0004 (Students Journal of Economic and Management, 2015)
This study analyzed the influence of Motivation, Career Development, and Discipline to Employee Performance. The research object in this paper is Bank Jateng branch of Pati. Sampling technique in this study is the use of random sampling of 77 respondents in the sample by using the method of data collection questionnaire (questionnaire) by distributing a list of questions to respondents in order to obtain information. The purpose of the study was formulated to determine the influence of motivation, career development, and discipline to employee performance. The data were analyzed using factor analysis to test the validity of the question items, cronbach alpha formula to test the reliability of the instrument, regression analysis to test the influence of each partial independent variables. The results of the research are: (1.) Motivation has a positive and significant influence to employee performance. (2.) Career Development has a positive and significant influence to employee performance. (3.) Discipline has a positive and significant influence to employee performance. Keywords : Motivation, Career Development, Discipline, andÂ  Employee Performance